PROBLEMS OF DEVELOPMENT AND SOLUTION OF TECHNOLOGICAL PROCESSES OF CLEANING COTTON WITH SMALL DISPERSION PARTICLES AND DUST - S?bitkh?n Hashimov, Irisqulov Farxod Sultonboyevich, Imamnazarov Erkin Dexkanaliyevich, Erkinov Husniddin Bakhtiyoro’g’li, Abdujalilov Sodiqjon Muhammadamino’g’li (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The article highlights the importance of the cotton industry of the Republic in Uzbekistan’s economy and its development, making it one of the leading cotton producing countries in the world. It analyzes the results of scientific work done by researchers in the field of high-quality fiber and highlights the fact that high fiber quality is largely dependent on cotton-cleaning technology. In addition, it has been recently reported that foreign countries, including China (China), have been interested in Uzbek cotton, and that their experts have been critical of the Uzbek cotton fiber, and that it contains "neps" in the fiber, resulting in poor quality of Uzbek cotton. In order to overcome this problem, this article proposes a computer model of a device for the treatment of seedycotton, based on a completely new cotton cleaning technology. This technology is described in detail in order to preserve the natural state of the cotton seeds being cleaned and not to damage the seeds during cleaning.